Cannabidiol (CBD): Potential Use in Otorhinolaryngology - Geraldo Pereira Jotz; Rafael Scorsatto Ortiz; Renata Pereira Limberger; Flavio Anastácio de Oliveira Camargo (2024)
Cannabidiol (CBD) is an oily extract from the Cannabis sativa plant that is not prohibited, not psychoactive and has been allowed for medicinal use in Brazil since 2015. This cannabinoid has a calming and relaxing effect and is therefore used as an herbal medicine for a wide range of symptoms, particularly in cases of refractory epilepsy. There is also evidence of anticonvulsant, neuroprotective, anti-inflammatory, antitumor, antipsychotic, and anxiolytic effects, as well as effects on functions such as metabolic regulation, movement and coordination, appetite, sleep, mood, pain, reward systems, reasoning and memory, bone growth, and immune function. This cannabinoid has been very prominent in Brazil, in terms both of its use, production, and legislation and of its potential for research and therapy. Despite this evidence, there are few references about the effect of CBD on otorhinolaryngological diseases. This editorial aims to promote understanding and the advancement of studies in this field, with case reports of the use of this cannabinoid in otorhinolaryngology.[1]